European urban freight transport policies and research funding: Are priorities and H2020 calls aligned? - Giacomo Lozzi; Valerio Gatta; Edoardo Marcucci (REGION, 2018)
The European Commission has recently developed a growing awareness with respect to the challenges urban freight transport (UFT) poses to cities and, consequently, has started defining specific policies and promoting dedicated tools to address them. Transport is a shared responsibility between the European Union and the Member States, where the subsidiarity principle applies. Accordingly, the former provides European local authorities with support in different areas, including research and innovation funding. This paper aims to assess the linkage and consistency between European policy priorities for UFT and the corresponding calls of the Horizon 2020 (H2020) Research Programme, created to foster research and innovation. The paper identifies and extrapolates in a comparable format ten UFT priority solutions and estimates their degree of correspondence with the H2020 Work Programmes using the amount of research funds allocated to each of them as a proxy. Findings show that, generally, the European Commission addresses UFT through a systematic and coherent approach. Moreover, all the identified solutions are covered by at least one H2020 call, although the extent of the coverage is heterogeneous. Four of the UFT solutions present an overall consistency when it comes to comparing the extent of the scope of the solution and the number of policy documents addressing it, on the one hand, and the number of calls considering it and the budget (potentially) available, on the other.
Keywords: 330; Horizon 2020; urban mobility; urban freight transport; European Union; transport policy